1999
DOI: 10.1016/s0002-9440(10)65257-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene Amplification and Overexpression of CDK4 in Sporadic Breast Carcinomas Is Associated with High Tumor Cell Proliferation

Abstract: Amplification of the cyclin-dependent kinase 4 (CDK4) gene, located at 12q13-q14, has been found as an alternative genetic alteration to CDKN2A inactivation in various human tumors including malignant gliomas and sarcomas. In the present study, we have evaluated the frequency of the CDK4 gene amplification in sporadic breast cancer by applying a nonradioactive quantitative differential polymerase chain reaction based on fluorescent DNA technology. Fluorescent-labeled polymerase chain reaction products were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(86 citation statements)
references
References 25 publications
7
77
0
2
Order By: Relevance
“…Surprisingly, Morris et al (2002) have shown that the CDK4(R24C) produced no additional growth advantage compared with CDK4 overexpressing forms in human fibroblasts; indeed CDK4(R24C) was less effective than wild-type CDK4 (Morris et al, 2002). These results support the observation that CDK4(R24C) mutation is restricted to melanoma development where escape of the p16 Ink4a inhibitory effect appear to be indispensable, while overexpression of CDK4 may be a more general mechanism for an acquired growth advantage (He et al, 1994;Schmit et al, 1994;Sonoda et al, 1995;Kanoe et al, 1998;An et al, 1999;Dei Tos et al, 2000;Lam et al, 2000).…”
Section: Discussionsupporting
confidence: 55%
“…Surprisingly, Morris et al (2002) have shown that the CDK4(R24C) produced no additional growth advantage compared with CDK4 overexpressing forms in human fibroblasts; indeed CDK4(R24C) was less effective than wild-type CDK4 (Morris et al, 2002). These results support the observation that CDK4(R24C) mutation is restricted to melanoma development where escape of the p16 Ink4a inhibitory effect appear to be indispensable, while overexpression of CDK4 may be a more general mechanism for an acquired growth advantage (He et al, 1994;Schmit et al, 1994;Sonoda et al, 1995;Kanoe et al, 1998;An et al, 1999;Dei Tos et al, 2000;Lam et al, 2000).…”
Section: Discussionsupporting
confidence: 55%
“…We did not investigate abnormalities in CDK4, which is also intimately associated with the G1 cell cycle checkpoint. However, An et al (39) described amplification of this gene in 15 of 95 (16%) breast cancers. It is tempting to speculate that CDK4 amplification may be responsible for cell cycle deregulation in many of the cases that express pRB, p16, cyclin D1, and p53 at normal levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cyclin D-Cdk4 titrates p27 and p21 to cyclin D-Cdk4, thereby triggering the activity of the cyclin E-Cdk2 holoenzyme (Sherr and Roberts, 1999). Consistent with their growth-promoting functions, the cyclin D1 and the Cdk4 gene were found to be amplified in many human cancers (Bartkova et al, 1995;An et al, 1999).…”
Section: Introductionmentioning
confidence: 99%